The S.Q.U.I.D. squad. #4, A battle begins : an unofficial graphic novel for Minecrafters - Miller, Megan, 1963- (Sky Pony Press, 2021)
"When Pillagers establish an outpost not far from the Book Guardian's hidden ravine headquarters, it's time for the S.Q.U.I.D Squad to swim into action. When their plans to outwit and scare the Pillagers fail, they must turn to the help of a mysterious captive of the Pillagers, the Talker. But the Talker seems to have devious plans of her own"--